The Importance of Maine for Ecoregional Conservation Planning - Baldwin, Robert; Trombulak, Stephen; Beazley, Karen; Reining, Conrad; Woolmer, Gillian; Nordgren, John; Anderson, Mark (Maine Policy Review, 2007)
Ecoregional conservation planning aims at protecting biodiversity within a realistic social and economic framework. The authors of this article suggest that Maine’s forests are the ecological core of the entire Northern Appalachian/Acadian ecoregion, which spans four states and five Canadian provinces. Using mapping and mathematical models of the “human footprint,” they note that Maine has a large, contiguous, undeveloped and unfragmented forest compared with neighboring states and provinces. However, compared with its neighbors Maine also has the largest proportion of unprotected forest. The authors conclude with the hope that land use policy and planning can be better informed through the active integration of recent ecoregional conservation mapping models